PENGARUH METODE MENGAJAR TERHADAP MINAT BELAJAR SISWA SEKOLAH DASAR PADA PELAJARAN MATEMATIKA - Syva Lestiyani Dewi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
The purpose of this study was to determine the relationship between the teaching methods used by the teacher and the students' interest in mathematics. This research is a quantitative study with data collection in the form of interviews, questionnaires and documentation of the transcripts of mathematics grades in one of the primary schools. There is a positive relationship between how teachers deliver Mathematics material to students' interest in learning Mathematics. This is used as a topic of discussion because in the learning process, students' interest in the subject is needed. The teaching and learning process which is supported by high interest and enthusiasm from students can make learning much more effective. This is also supported by the opinion of experts on how effective learning can be done, one of which is the relationship between appropriate and fun teaching methods with high student interest. In addition, the author raises the subject of Mathematics because this subject is still a frightening specter for students, especially the response that Mathematics teachers are usually scary and boring teachers. Therefore a study was made that shows how effective the relationship is between the Mathematics Teacher's teaching methods and students' interest in learning about this subject.